Nonuniform Changes in the Distribution of Visual Attention from Visual Complexity and Action: A Driving Simulation Study. (February 2015) - Park, George D; Reed, Catherine L
Researchers acknowledge the interplay between action and attention, but typically consider action as a response to successful attentional selection or the correlation of performance on separate action and attention tasks. We investigated how concurrent action with spatial monitoring affects the distribution of attention across the visual field. We embedded a functional field of view (FFOV) paradigm with concurrent central object recognition and peripheral target localization tasks in a simulated driving environment. Peripheral targets varied across 20–60 deg eccentricity at 11 radial spokes. Three conditions assessed the effects of visual complexity and concurrent action on the size and shape of the FFOV: (1) with no background, (2) with driving background, and (3) with driving background and vehicle steering. The addition of visual complexity slowed task performance and reduced the FFOV size but did not change the baseline shape. In contrast, the addition of steering produced not only shrinkage of the FFOV, but also changes in the FFOV shape. Nonuniform performance decrements occurred in proximal regions used for the central task and for steering, independent of interference from context elements. Multifocal attention models should consider the role of action and account for nonhomogeneities in the distribution of attention.